AN EVALUATION OF MATHEMATICS INSTRUCTION IN FOSTERING CREATIVE PROBLEM-SOLVING SKILLS AMONG GRADE 3 STUDENTS - Caroline Cindy Pratiwi; Stefanus Christian Relmasira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by field conditions where third-grade elementary school students often associate mathematics learning with feelings of fear, difficulty, and exhaustion, which ultimately hinders the emergence of Creative Problem Solving (CPS) skills. This study aims to describe students' problem-solving processes and difficulties, analyze the teacher's role as a facilitator, and evaluate the implementation of creative problem-solving instruction. A quantitative approach utilizing a Quasi-Experimental Design (Two-Treatment Design) was employed. The research sample consisted of a student group at SDN Jogoyasan receiving the Problem Based Learning (PBL) model and a student group at SDN Keditan receiving the Discovery Learning (DL) model. Data were collected through test techniques (pretest-posttest) and non-test methods (Y-Chart reflection instrument), which were analyzed statistically using SPSS and qualitatively using MAXQDA 2020 software. Hypothesis testing results revealed that both learning models had a highly significant effect on improving students' CPS abilities (p < 0.001). The PBL class experienced a Gain Score increase of 20.71 points, while the DL class increased by 18.46 points. Qualitative findings indicated that the use of concrete learning media and the creation of a Joyful Learning environment effectively transformed negative emotions into metacognitive awareness (Mindful Learning), making students braver and more enthusiastic in exploring problem-solving strategies. In conclusion, the integration of PBL and DL models with a Deep Learning approach is effectively implemented to enhance the CPS skills of third-grade elementary school students.